STUDI TENTANG FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS STRATEGI BERSAING UNTUK MENINGKATKAN KINERJA PERUSAHAAN PADA KUKM PENGRAJIN KULIT DI MANDING - BANTUL - Barokah, Siti Nur (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2008)
In a context of enhancing the competitive advantage, acquiring knowledge is an important factor. This point is the weakest of the KUKM powerlessness. The problem that Group of Small Business and Enterpreneurs often face basically is on the decision making on Competitive Strategy in order to enhance the firmsâ€™ performance. Therefore, it is necessary to examine â€œHow to enhance the Group of Small Business and Enterpreneursâ€™s performance, by focusing on Competitive Strategy and the affecting factors.â€ Hence, a model that consists of five variables is developed. Those five variables are strategic assets, environment adaptability, entrepreneurship orientation, competitive strategy and firmsâ€™ performance.Data of observed variables is collected through questionnaire. The questionnaire is specially developed to have structured questions about the variables. 100 respondents of owners or people who run leather crafts in Yogyakarta were asked to answer the questionnaires. Then, data collection is analyzed with Structural Equation Modeling (SEM) method.The test result of the model shows that the model developed in this researched is proven to be fit. While the hypothesis test shows that the quality of strategic asset, environmental adaptability, and the quality of competitive strategy has a positive and significant effect on firmsâ€™ performance.Based on the hypothesis result, enhancing Group of Small Business and Enterpreneurs performance can be achieved by making better the competitive strategy through entrepreneurship orientation.